Comparative Outcome of Obesity in Ischemic Heart Disease a Clinical Study - Imran Javaid, Munir Ahmed Rashi, Aamna Khokhar, Ratan Kumar, Syed Ahsan Raza, Bilal Mustafa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the comparative outcome of obesity in ischemic heart disease. Duration of Study: July, 2021 to Dec, 2021 Place and Duration: CCU department D.G. Khan Medical College and Teaching Hospital Dera Ghazi Khan Methods: This research included 180 participants of both sexes. Patients were between the ages of 22 and 80 years old, according to the study. As part of their informed written permission, researchers collected demographic information such as age, sex and BMI. Patients were divided in two groups, group I had 90 obese patients and group II had non obese 90 patients. Follow up among patients were taken in duration of 12 months. Both groups’ outcomes were evaluated and compared in terms of increase in risk factor of IHD, myocardial infarction and mortality because of these factors. SPSS 22.0 was used to analyze complete data. Results: There were 55 (61.1%) males and 35 (38.9%) females in group I and in group II 46 (51.1%) males and 44 (48.9%) females in group II. The mean age of the patients in group I was 41.4±11.62 years and had mean BMI 32.14±21.86 kg/m2 while in group II mean age was 38.41±12.42 years with mean BMI 25.2±11.34 kg/m2. 40 (44.4%) patients in group I and 45 (50%) patients in group II was educated. In group I 25 (27.8%) patients were smokers, 19 (21.1%) patients had DM and in group II 27 (30%) were smokers and 5 (5.6%) cases had DM. We found increase in Ischemic heart disease in 65 (72.2%) cases of group I and in group II IHD was found in 11 (12.2%) cases. Frequency of Myocardial Infarction was also higher in obese patients than non-obese cases. Systolic and diastolic blood pressure was also higher in obese patients. HDL was lower in obese patients while cholesterol, LDL, triglycerides and CRP was found higher in obese patients. Mortality in obese patients with IHD was 12 (13.3%) but no any mortality found in non-obese cases. Conclusion: In this study we found that obesity and increase in weight is a significant risk factor for ischemic heart disease and myocardial infarction and because of these diseases patients had poor outcomes with increase in rate of deaths.